Gendering trauma and healing in a post-conflict environment : Las Dignas, mental health, and the empowerment of Salvadoran women - Leslie, Helen Margaret (Massey University, 1999)
There is no doubt that the experience of war, be it war between nation states or civil war, varies considerably for both male and females. The twelve year civil war in El Salvador was no exception. Salvadoran women who worked in various sectors as combatants, urban collaborators, home-makers, nurses, cooks or radio operators for the guerrilla forces, experienced the war and now experience so-called peace, in ways that relate directly to the construction of the female sex in Salvadoran society. As a result of these gendered experiences many Salvadoran women are suffering trauma despite the cessation of the war in 1992. This trauma acts to disempower these women and to prevent them from actively participating in the important processes of post-conflict reconstruction currently taking place in Salvadoran society This thesis aims to analyse the approach taken by one Salvadoran organisation for feminist political action, Las Dignas, in healing the trauma of Salvadoran women. Reviewing relevant literature on gender and development theory and gender and conflict theory, and drawing on feminist methods in the fieldwork context, it will show how the healing process employed by Las Dignas is empowering Salvadoran women at both personal and socio-political levels. The conclusions derived from this research process are as follows. Firstly, by incorporating mental health into their gender and development programme, Las Dignas has recognised the importance of a gendered approach to healing in the post-conflict context. This form of approach has the potential to empower women to reconstruct their gendered identities so that they are able to actively participate in efforts to eradicate the machismo, inequality and poverty that continues to plague Salvadoran society. Secondly, because it is evident that a gendered approach to healing has been successful in empowering women in post-conflict El Salvador, there is a need to integrate the concept of empowerment into mental health interventions for women in the numerous post-conflict environments that also exist in today's world.
Keywords: Las Dignas Mujeres por La Dignidad y La Vida; Women; Women in politics; Mental health; Post-traumatic stress disorder; Social change; Politics and government; Social conditions; El Salvador